Closed-system solid surface vitrification versus slow programmable freezing of mouse 2-cell embryos - Vutyavanich T. (2014)
Purpose: To compare closed-system solid surface vitrification with slow freezing. Methods: Mouse 2-cell embryos (n=348) were divided into vitrification, slow freezing and non-frozen groups. For vitrification, embryos were exposed to 10% ethylene glycol (EG), 10% dimethylsulfoxide (DMSO) and 10% fetal bovine serum (FBS) in phosphate-buffered saline (PBS) for 10 min, then transferred into 17.5% EG, 17.5% DMSO, 0.25 M trehalose and 10% FBS in PBS. They were placed on hemi-straws and inserted into 0.5 ml straws inside a previously cooled aluminum cylinder. Slow freezing was done in straws by the conventional method. Results: Vitrified embryos had significantly higher survival, further cleavage and blastocyst formation rates than those in the slow freezing group (p<0.001) and were comparable to controls. Blastocysts in the vitrification and control groups had significantly more cells than those in the slow freezing group (p<0.05). Conclusions: Closed-system vitrification was more effective than conventional slow freezing. © 2009 Springer Science+Business Media, LLC.